2014
DOI: 10.1111/1365-2656.12307
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effects and population regulation: maternal density‐induced reproduction suppression impairs offspring capacity in response to immediate environment in root voles Microtus oeconomus

Abstract: The hypothesis that maternal effects act as an adaptive bridge in translating maternal environments into offspring phenotypes, and thereby affecting population dynamics has not been studied in the well-controlled fields. In this study, the effects of maternal population density on offspring stress axis, reproduction and population dynamics were studied in root voles (Microtus oeconomus). Parental enclosures for breeding offspring were established by introducing six adults per sex into each of 4 (low density) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 63 publications
3
44
0
1
Order By: Relevance
“…FCM is primarily derived from plasma‐free CORT in rodents (Palme, Rettenbacher, Touma, El‐Bahr, & Möstl, ). Our previous study validated that measurement of the FCM level is a reliable method to assess the physiological state and stress level of root voles (Bian et al., ; He et al., ).…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…FCM is primarily derived from plasma‐free CORT in rodents (Palme, Rettenbacher, Touma, El‐Bahr, & Möstl, ). Our previous study validated that measurement of the FCM level is a reliable method to assess the physiological state and stress level of root voles (Bian et al., ; He et al., ).…”
Section: Methodssupporting
confidence: 71%
“…Specifically, we have found that high population density is associated with a significantly elevated stress response in both parents and offspring (Bian et al., ; Du et al., ). Density stress during the maternal phase significantly suppresses offspring reproduction function and decreases offspring body size at sexual maturity and the physiological condition in offspring under maternal stress (Bian et al., ). Similar to those characteristics that can be observed in other species (Nelson, Asfaw, DeVries, & Demas, ; Sinclair & Lochmiller, ), density stress in root voles is associated with an immune suppression and a prevalence of parasitic infection.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The consequences of maternal stress have long been considered to be maladaptive in biomedical fields because offspring phenotypes that can occur in response to maternal stress (e.g., smaller size, slower growth, lower energetic demand, higher anxiety‐like behavior) are assumed to confer reduced fitness (Sheriff & Love, 2013). However, researchers have recently proposed that maternal stress can play adaptive roles across a wide variety of animal taxa if stress‐induced phenotypes better prepare offspring for a stressful postnatal environment in mammals (Bian et al., 2015; Dantzer et al., 2013; Sheriff, 2015; Sheriff, Krebs, & Boonstra, 2010), birds (Chin et al., 2009; Coslovsky & Richner, 2011; Love, Chin, Wynne‐Edwards, & Williams, 2005; Love & Williams, 2008), reptiles (Bestion, Clobert, & Cote, 2015; de Fraipont, Clobert, John‐Adler, & Meylan, 2000; Meylan & Clobert, 2005), and fish (Giesing, Suski, Warner, & Bell, 2011). Despite this recent progress, a unified framework that both explains the selective mechanisms and allows field‐testing of the adaptive role of maternal stress has yet to be proposed.…”
Section: Introductionmentioning
confidence: 99%
“…While these effects of prenatal stress in offspring have been extensively investigated in laboratory rats using usually conventional laboratory stressors (e.g., physical restraint, Maccari et al, ; electric foot shock, Estanislau & Morato, ; psychological stress, Abe et al, ; and psychosocial stress, Götz & Stefanki, ), comparatively fewer studies have involve wild species and ecologically relevant stressors (Sheriff et al, ). Examples of this last situation in rodents were carried out by Bian and colleagues (), who studied the effects of maternal population density on offspring physiology, reproduction and population dynamics in root voles ( M. oeconomus ), and Dantzer et al () who found that density‐induced maternal stress in red squirrels ( Tamiasciurus hudsonicus ) results in faster growing offspring through an adaptive hormone‐mediated maternal effect. Natural stressors, like the presence of a predator or cues indicative of its presence, which certainly represent an ecologically more relevant stimulus, are comparatively less used as stressors in experimental laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%